Debt restructuring in Ukraine - Yushynova, O. (ТДАТУ, 2018)
In conclusion it should be noted, that on the way of integrating Ukraine into Europe in order to conduct debt restructuring, attract investments into entities, improve economic relations it should strictly follow the accepted restructuring law for gaining benefits in economic and social spheres
Keywords: Ukraine; debt restructuring; financial institution; shareholders